Effect of nitrogen fertilization on the protein quality of timothy grass and silage - Liisa Syrjälä-Qvist (Agricultural and Food Science, 1984)
Timothy grass given N fertilizer at the rates of 40, 80 and 120 kg N/ha was preserved in 3 glass-fibre silos of 0.4 m3. The crude protein content of DM in the grass increased with the increase of N fertilization as follows: N40 14.8 %, N80 18.4 % and N120 22.1 %, but the proportion of true protein in crude protein decreased: N40 82 %, N80 78 % and N120 76 %. The proportion of watersoluble N in the total N in the grass was: N40 27 %, N80 30 % and N120 33 %. The higher was the N fertilization level, the more rapidly was the protein of the grass degraded in the rumen. The amino acid profile of the protein was similar at all the N fertilization levels. The quality of all the silages was good. The NH3-N fraction of total N was 2.8—3.9 % and the proportion of water-soluble N in total N was 51—55 %, In silage the decrease during ensiling in the proportion of true protein in crude protein and the increase in the proportion of water-soluble N in total N were smaller than in the other silages. The rumen degradability of protein during the first two hours was also lowest in this silage.